Kajian Optimalisasi Peran Balai Penyuluh Pertanian dalam Pembangunan Pertanian di Kabupaten Bekasi - Pipit Septi Fitriyanti; Rizky Afnan Fadillah; Fauziah (Bekasi Development Innovation Journal, 2024)
Implementation of the roles and functions of BPP with the strengthening of BPP as a data and information center, a movement development center, a learning center, an agribusiness consulting center, and a partnership network development center. However, there are challenges in the agricultural sector in Bekasi Regency, namely the decreasing amount of agricultural land, population growth, land use change for agriculture, the growth of new housing, and others. Therefore, a study on the Optimization of the Role of Agricultural Extension Centers in Agricultural Development in Bekasi Regency is needed. This study uses a mixed methods approach, both quantitative and qualitative, and a participatory approach is used to obtain facts and problems as well as priority development sequences and input from various stakeholders to complement the analysis results. Agricultural Extension Centers in carrying out their roles and functions have several problems, including the lack of facilities and infrastructure of Agricultural Extension Centers (BPP) as an institution in agricultural empowerment, the lack of Human Resources (HR) in conducting agricultural extension activities, and the lack of budget in agricultural extension activities. The government must pay more attention to agricultural extension programs throughout Bekasi Regency, the role of extension workers in carrying out activities must be continuous, the things that should be the focus of development include facilities and infrastructure, Human Resources (HR), capacity building of agricultural extension workers, and costs or budgets as optimization of Agricultural Extension Centers in the development of Bekasi Regency. Keywords: Penyuluh Pertanian, Sarana, Prasarana